Rendimiento volumétrico de la especie Dipteryx micrantha. Harms, "shihuahuaco" en el proceso de aserrío considerando su tipología y dimensiones en la empresa Consorcio Forestal Loreto SAC, Loreto - Maynas - Iquitos - 2021 - Isuiza Rojas, Christian Tito (2022)
The research work was carried out in the company Consorcio Forestal Loreto SAC, located in Iquitos Nauta highway km 2.5, in order to determine the volumetric yield of the Dipteryx micrantha species. Harms; Shihuahuaco in the sawmill process considering its typology and dimensions. From the results obtained, it can be noted that the yield is 58,08% and the by-products reached 41,92%. The long comercial wood reached 36,76% while the lomg narrow reached only 0,96% the short wood t14,57% and the slatwork 5,79%. The first quality of commercial long wood reached 56.85% of the total obtained (359,67 m3), the second quality 19,84% (125,56 m3) and the third quality 12,70% (80,34 m3) and the national market wood only 10,61% (67,14 m3). Long narrow comercial lumber totaled 443,27 m3 and 2 inch thick lumbertotaled 205,95 m3. The highest number of pieces of 1-inch-thick sawn Wood of the shihuahuaco species was obtained in length 10 with 23,61% and the highest volumen in length 13 with 96,25 m3. The highest number of pieces of 2-inch thick sawn wood of the shihuahuaco species was obtained in length 11 with 26% and the highest volumen in length 11 with 66,43 m3. The shape coefficient of the shihuahuaco species was 0,88% and the taper was 0,7 cm/m to 13,1 cm/m, depending on the length of the shaft, which normally fluctuates between 9 to 10 meters long cm/m.